An evaluation of small satellite technology transfer and capability-building in Algeria - Ayad, A (Cranfield University, 2018)
The potential for satellite technology to make an essential contribution to socio-economic development has been recognised by the international community since the onset of space adventure in the late 1950s. Due to its complexity and the resources required, satellite technology development has always been the reserve of major powers. However, a new trend emerged in the 1990s towards developing smaller and cheaper satellites. It is driven by the spectacular development in information and communication technologies, advances in technology miniaturisation, rising performance of off-the-shelf components, and space sector globalisation. This trend has lowered barriers to entry for small developing countries. They have used the new mechanism of small satellite collaborative projects in order to transfer Earth observation small satellite technology from developed countries. Like other developing countries, Algeria has leveraged this trend and engaged successively in three Earth observation small satellite collaborative projects with foreign companies in order to build small satellite capability. The purpose of this study is, thus, to evaluate whether Algeria has skilfully combined the technology acquired from abroad with local efforts to build effective and sustainable local small satellite capability. Technological capability-building through technology transfer usually refers to the ability to reconcile two categories of factors: i) exogenous factors, external to the country’s socio-economic environment, that condition the transfer of technology from abroad - these factors are traditionally gathered under the body of knowledge called ‘technology transfer’; and ii) endogenous factors, relating to the local effort to effectively acquire and indigenise the transferred technology – these factors are traditionally gathered under the body of knowledge called ‘technological capability-building’. Technological capability-building through technology transfer is also viewed as a learning process where knowledge is transferred from abroad and locally diffused. The evaluation approach adopted in this study examines the small satellite capability-building programme from a knowledge-oriented perspective. Algeria’s ii context is appraised by using the Innovation System analytical approach. The programme planning is evaluated by using the ‘strategic planning’ analytical approach. The programme implementation is evaluated by placing technological learning at the heart of the study. Two systemic models for the evaluation of knowledge flow from the transferor to the transferee, and then to its local environment, have been devised and tested. The knowledge-oriented perspective has been triangulated with perspectives stemming from the two traditional bodies of knowledge: technology transfer and technological capability-building. The evaluation has been comprehensive by taking into account factors across different levels of analysis: individual and team (micro level); organisation or firm (meso level); and national, sectoral and international (macro level). The evaluation has been performed through a mixed method research design. The research findings indicate that the process of building small satellite technological capability in Algeria has provided mixed results, and the most concerning are at the macro level. Algeria has failed to establish a strong foothold between the nascent satellite development activities and a local supply chain. Moreover, at the meso level, Algeria has not established an effective learning organisation that can lead, synergistically and coherently, satellite development activities. Finally, at the micro level, Algeria has failed to align technology transfer mechanisms with satellite development objectives. Based on these findings, the study highlights the need for clear strategies with prioritised objectives. It recommends elevating management capability-building as an absolute priority, and suggests the adoption of appropriate technology transfer mechanisms and a diversified projects portfolio.
© Cranfield University, 2018
Keywords: Small satellites; Developing countries; Technology transfer